Ayurvedic soaps or Ayurvedic shower gels: Which is more effective? - Manju M, Prabha; Austin, Dr. Anoop; Prabhu, D. K. Srinivasa (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Bar soaps are traditionally been one of the most commonly used means of hand sanitation, particularly since the advent of antimicrobial hand soaps. It has been demonstrated that soaps that do not contain agents that are antimicrobial in nature are seldom effective in decreasing the bacterial population present on the skin. Shower gels are higher viscosity variants of foam baths, often containing higher levels of active materials. Efficacy of herbal extracts and the extracts incorporated in formulations like soap and shower gel were evaluated. Vipruthi oil with 3 herbal extract components, Lakshadi oil, Eladi oil and Sandalwood oil were the extract formulations taken for antimicrobial efficacy testing. These extract formulations were individually tested for their efficacy against common pathogens and the same were incorporated in soap and shower gel formulations. The efficacy against S. aureus, S. pneumoniae, S. epidermidis, P. aeruginosa and C. albicans culture were evaluated by Zone of inhibition and Minimum inhibitory concentration test. Mean and standard deviation were used for statistical analysis. The Extract component I was found to be effective (100 microlitre (µl)) showing clear ZOI and MIC of 0.1 milligram/millilitre (mg/ml) against S. pneumoniae. The soap formulation with sandal and eladi oil was showing MIC of 0.5 mg/ml against S. aureus whereas the body wash with sandal and eladi oil was inhibitory at 2.5 mg/ml. Thus both soap and body wash formulations were found to be more or less similarly effective against selected pathogens.